Critical Analysis of Healthcare Resource Distribution, Cost-Effectiveness, And Equity - Al Wosibei, Ahmad Abdulwahab Taher; Alabdulwahed, Majed Fahad Mohammed; Abdularhman, Ibrahim Bu Saad; Saeedain, Jaffar Mohammed Ahmed; AlSadiq, Maram Ali Abdullah; Altalaliwah, Ali Salman H; Al-Ghamdi, Mohammed Saeed; Aldossary, Amenah; Alshikh, Zainab Mohammed; AlQattan, ALi Essa (Journal of Ecohumanism, 2024)
This paper aims to critically analyze the distribution of care resources, costs, and their effectiveness and equity. Currently, the healthcare industry has registered different challenges, such as escalating costs, an ageing population, growing healthcare demands, and differing resource distributions worldwide. The ratio between resources and healthcare outcomes has, therefore, become important to review. Critically discussed are the spatial allocation of healthcare resources, the techniques for comparing costs and effects, and the approaches to implementing fair resource access and health service provision at national and international levels. This contemporized review of literature, based on case studies across the globe, compares and contrasts equitable and effective hospital resource allocation, especially among LMICs. This paper identifies gaps in access and health inequities as emerging as major issues of concern despite improvements in resource utilization and cost containment. Suggestions are given to the policymakers on how the improved models of efficiency and fairness can be developed in health care systems.